Taxonomia de Papilionoideae (leguminosae) da Mata Atlântica do Rio Grande do Norte, Brasil - São-Mateus, Wallace Messias Barbosa (2013)
Leguminosae is the third largest family of angiosperms with about 19.325 species and 727 genera, and it is pantropically distributed. Papilionoideae is the most diverse of the three legume subfamilies, with around 13.800 species (71%), 478 genera, and 28 tribes. Papilionoid legumes include herbs, shrubs, lianas or trees with pinnate, trifoliolate, unifoliolate or simple leaves, flowers frequently papilionate with descending imbricate petal aestivation, the petals highly differentiated into standard, keel, and wings, androecium usually diplostemous, and seeds without pleurogram, with conspicuous hilum, and the embryo radicle usually curved. The current study aims to carry out a taxonomic account of the Papilionoideae from Atlantic Forest remnants in Rio Grande do Norte, Brazil, across the herbaria data surveys, collections of field samples and morphological analysis of the collected specimens and/or herbaria materials. Identification key, descriptions, diagnostic characters, illustrations, and geographic distribution of the 68 species and 32 genera within the following tribes Phaseoleae (11 genera/24 species), Dalbergieae (9/20), Swartzieae (3/3), Millettieae (2/4), Sophoreae (2/2), Abreae (1/1), Crotalarieae (1/3), Desmodieae (1/7), Indigofereae (1/3), and Sesbanieae (1/1). The most species-rich genera were Desmodium Desv. (7 species), Centrosema (DC.) Benth. (5), Stylosanthes Sw. (5), Aeschynomene L. (4) and Macroptilium (Benth.) Urb. (4). Concerning to the habit, the herbaceous and shrubby has predominated with 60% (41 spp.), following by the vine and lianas with 28% (19 spp.) and the woody with only 12% (8 spp.). Thirty two species and the following genera are newly recorded for the flora of Rio Grande do Norte: Chaetocalyx, Cochliasanthus, Crotalaria, Galactia, Geoffroea, Macroptilium, Rhynchosia, Swartzia, Trischidium, and Vigna